Stabilization and Solidification of Produced Tailings in the Lead Extraction Process Using Brine Leaching Method - Ravanbakhsh Shirdam; Atefeh Nezami (محیط زیست و توسعه فرابخشی)
Introduction: Brine leaching tailings (BLT), produced from the pilot scale extraction of lead from zinc filter cakes, contain concentrations of heavy metals that surpass established threshold limits. Prior to the construction of a lead extraction facility, it is imperative to identify a method that is technically viable, economically sustainable, and environmentally benign. The primary aim of this research is to diminish the solubility of metallic elements in BLT through the application of stabilization and solidification (S/S) techniques, incorporating additives such as cement, silica fume, and sand.Materials and Methods: While assessing the physical properties of BLT, their chemical characteristics, including heavy metal content, were analyzed using ICP-OES and oxide compositions were determined via XRF. To decrease the solubility of heavy metals, particularly lead, the S/S method was applied to these tailings. In this context, to achieve the necessary strength in the tailings, 16 mixtures containing tailings with varying additions of cement (0-10%), silica fume (0-1.5%), and sand (0-10%) were designed using DX7 software. Cubic samples were prepared with a water to powder ratio of 0.4 (w/p=0.4). These cubic specimens (5×5×5 cm) were tested to assess their compressive strength at 7 and 28 days. The 7-day and 28-day samples from mixture Ni16, which exhibited the highest compressive strength, underwent the TCLP using EPA Method 1311. Subsequently, heavy metals in the TCLP extract were quantified using EPA Method 6010D via ICP-OES. Additionally, to qualitatively and quantitatively analyze the original tailings and the S/S-treated tailings, XRD testing was conducted.Results: The major concentrations of elements in BLT exceed their permissible limits in the tailings. Moreover, the TCLP test of the control sample indicated that the concentration of lead in the extract (6.11 ppm) surpassed its permissible limit. Consequently, it is essential to reduce the solubility of the waste elements through the S/S method before disposal. The compressive strength of the mixtures at 7 and 28 days ranged from 2 to 5.2 MPa and 2 to 9 MPa, respectively, exceeding the minimum required compressive strength of 0.35 MPa. The concentrations of all heavy metals in the extracts from two S/S samples, N15 and N16, were below their permissible limits, thus validating the effectiveness of the applied S/S method. Analysis of the S/S tailings and the S/S sample (Ni16) revealed the formation of new minerals such as Gypsum, C-S-H (Calcium Silicate Hydrate), Ettringite, and Calcium Silicon. These minerals, resulting from the use of silica fume and cement and the hydration products of cement with the tailings, are likely contributors to the enhanced compressive strength of the samples.Discussion: While clarifying the negative impact of sand on the strength of the mixtures, it was observed that the percentages of cement and silica fume had a direct correlation with the compressive strength of the samples. Notably, the slope of changes in compressive strength per cement was substantially higher for the 28-day samples compared to the 7-day samples. One of the factors leading to the reduced short-term compressive strength of the mixtures can be the presence of heavy metals in the tailings. These metals interfere with the hydration reaction, thereby preventing the effective formation of silicate gel.